Asynchronous warming and δ(18)O evolution of deep Atlantic water masses during the last deglaciation - Zhang, Jiaxu (Proc Natl Acad Sci U S A, 2017)
The large-scale reorganization of deep ocean circulation in the Atlantic involving changes in North Atlantic Deep Water (NADW) and Antarctic Bottom Water (AABW) played a critical role in regulating hemispheric and global climate during the last deglaciation. However, changes in the relative contributions of NADW and AABW and their properties are poorly constrained by marine records, including δ(18)O of benthic foraminiferal calcite (δ(18)O(c)). Here, we use an isotope-enabled ocean general circulation model with realistic geometry and forcing conditions to simulate the deglacial water mass and δ(18)O evolution. Model results suggest that, in response to North Atlantic freshwater forcing during the early phase of the last deglaciation, NADW nearly collapses, while AABW mildly weakens. Rather than reflecting changes in NADW or AABW properties caused by freshwater input as suggested previously, the observed phasing difference of deep δ(18)O(c) likely reflects early warming of the deep northern North Atlantic by ∼1.4 °C, while deep Southern Ocean temperature remains largely unchanged. We propose a thermodynamic mechanism to explain the early warming in the North Atlantic, featuring a strong middepth warming and enhanced downward heat flux via vertical mixing. Our results emphasize that the way that ocean circulation affects heat, a dynamic tracer, is considerably different from how it affects passive tracers, like δ(18)O, and call for caution when inferring water mass changes from δ(18)O(c) records while assuming uniform changes in deep temperatures.